Astudy of bakeries in Al-Dayim using Markov chains - د. ابتسام محمد عبد الباقي عبد الله (White Nile Journal for Studies and Research, 2020)
This study aimed to find out the reasons that lead to the changes in market trends and the movement of customers between bakenes, and their future predictions. The researcher followed the stochastic processes approach for forecasting (transition matrix in Markov Chains). It is found that sales quotas for bakeries in the central market, neighborhoods, and industrial zone respectively 15% 62%, 23%. The study also predicted the shares according to the competitive position and future strategies and found the share for the market, neighborhoods, and industrial zone as follows: 16%, 62%, and 22%, respectively. The study found out that the percentage of those who complains from taxes 36.7% while the proportion of those suffering from power shortages, water scarcity, and high prices of flour and fuel is 60%, so the study recommends considering these problems.